HOUSING FINANCE- A STUDY ON CUSTOMERS’ PERCEPTION - Mathew Jacob (MIRROR, 2018)
Commercial banks in public and private sector have been playing an important role in housing finance for the last one decade. All public sector banks and private sector banks are now emerging as lenders in the segment, taking a slew of initiatives in the form of opening dedicated outfits / cells to cater to the ever- increasing demand for housing loans, offering competitive interest rates with fixed/variable options, waiver of processing fee, free additional attractive packages and flexibilities in housing loan schemes. Generally the traditional trend of the term “Housing Loans” or “Housing Finance” means finance for buying or modifying a property. A study of the housing loan schemes offered by public sector banks and private sector banks would pave the way for taking certain policy decisions for improving these housing loan schemes. The present study is an attempt to evaluate the housing finance provided by public sector and private sector banks in Kolenchery in Kunnathunad Taluk. The study has been undertaken mainly to highlight the features of housing loans offered by public and private sector banks in Kolenchery town in Kunnathunad Taluk. A sample of 100 borrowers representing various types such as Businessmen, Agriculturists, Government Employees, Employees of Private Enterprises, Professional People and Self-employed People of Canara bank and the HDFCs Bank. It is found that there is no difference in the rate of interest and repayment methods in public and private sector banks. There are differences in following the formalities at the time of lending, in offering incentives to the borrowers at time of lending, in service charges, in processing charges and in treating the customers in public and private sector banks. The Chi-square statistics provided different values, which were significant in both public and private sector. Therefore, the influencing factors to avail housing loan are different for customers public and private sector bank